Research nature and concepts "competitive enterprise" - Posokhov, Igor Mikhailovich; Chepizhko, E. V. (SCIEURO, 2016)
The article studies and analyzes various approaches to the definition of «competitiveness» and «enterprise competitiveness». The analysis revealed the general features of the selected definitions, their classification, identified the advantages and disadvantages, it was noted the need for further study of this category in the modern conditions market uncertainty, it was proposed a new definition of competitiveness of company.
Keywords: competition; competitiveness; enterprise competitiveness; production competitiveness; competitive advantage; competitive potential